HUBUNGAN MEKANISME KOPING DENGAN KUALITAS TIDUR PADA PASIEN HCU DI RSUD NGIMBANG KABUPATEN LAMONGAN - Salsabilah, Shofiyah; Maghfiroh, Isni Lailatul; Hanafi, Aprelia Afidatul (Coping: Community of Publishing in Nursing, 2024)
Patients are hospitalized often experience impaired sleep quality, especially in patients with critical conditions resulting from failure to adapt to a new environment such as patients in the High Care Unit (HCU). This study aims to determine the relationship between coping mechanisms and sleep quality in HCU patients at Ngimbang Hospital. This study used a correlational analytic design with a cross-sectional approach on 35 patients at Ngimbang Hospital, which were taken using consecutive sampling techniques in March-April 2023. Data were collected using a questionnaire on coping mechanisms and sleep quality. Data were analyzed using the pearson test. The results showed that 21 patients had maladaptive coping mechanisms and 14 patients had adaptive coping, while 31 patients had fairly good sleep quality, 3 patients had poor sleep quality and 1 patient had good sleep quality. The result of the statistical test was the Pearson correlation value of r s = 0,581 with a significance value of p = 0,000 meaning that there is a relationship between coping mechanisms and sleep quality in HCU patients at Ngimbang Hospital with a positive correlation strength. Coping mechanisms are needed in controlling one's emotions. This can cause anxiety so that it can result in good quality sleep. Other factors that can cause HCU patients to have moderate sleep quality are the environment such as the sound of monitors from other patients and room light. To improve the quality of good sleep, patients can self-identify emotionally so that anxiety does not arise which can lead to stress.